Interleukin-12p35 deficiency enhances mitochondrial dysfunction and aggravates cardiac remodeling in aging mice - Ye, Jing (Aging (Albany NY), 2020)
Our previous studies have demonstrated that interleukin-12p35 knockout (IL-12p35 KO) regulates the progression of various cardiovascular diseases, such as acute cardiac injury and hypertension. The aims of this study were to investigate whether IL-12p35 KO affects aging-related cardiac remodeling and to explore the possible mechanisms. First, the effects of IL-12p35 KO on heart structure and function were detected, and the results showed that IL-12p35 KO exacerbated cardiac remodeling and increased cardiac senescence-related protein levels in aged mice. In addition, whether IL-12p35 KO regulates cardiac senescence-related protein expression, cardiac mitochondrial dysfunction and cardiomyocyte apoptosis was also investigated. IL-12p35 KO increased mitochondrial calcium fluorescence intensity and ROS fluorescence intensity, while it reduced mitochondrial membrane potential. Furthermore, reduced mitochondrial complex (I-IV) activity and ATP levels and increased apoptosis-inducing factor (AIF)-related cardiomyocyte apoptosis were observed in aged IL-12p35 KO mice compared with wild-type mice. Our results demonstrate that aging is aggravated by IL-12p35 KO and that the mechanism may be related to exacerbation of mitochondrial dysfunction and AIF-related cardiomyocyte apoptosis.